Genocide of Rohingya Muslims: a classical model of ethnic cleansing - Osmani, Noor Mohammad; Hossen, Belayet; Shah, Qutub; U Tun Aung, Maulana Akbar Shah (International Institute of Islamic Civilisation and Malay World (ISTAC), IIUM, 2018)
Considerable historical evidence affirms that the Rohingya Muslims are indigenous inhabitants and rightful citizens of Myanmar, who have been living in Rakhine State not for decades, but for centuries. The Myanmar government has been systematically eradicating the Rohingya people due to their Islamic religious identity. This analysis finds that the ongoing persecution on Rohingya Muslims is a manifestation of a classical model of ethnic cleansing. The disasters experienced in Rakhine State present a complete evidence of systematic, widespread and prolific human rights violations, including heinous crimes against humanity. This article presents an academic perspective on repeated incidents, based on authentic proofs to international community of ethnic cleansing committed by the Myanmar army. This research has been carried out through various types of sources, such as recent and previously published books, articles, local and international newspapers, TV channels, magazines, documentaries, human rights organizations’ reports, and eye-witness accounts of the victims. Finally, it provides suggestions to resolve the rising problems, which may bring a permanent solution to the long-lasting humanitarian crisis in Rakhine State.